2010
DOI: 10.1021/ic101541q
|View full text |Cite
|
Sign up to set email alerts
|

Eu3+/Tb3+-Doped La2O2CO3/La2O3 Nano/Microcrystals with Multiform Morphologies: Facile Synthesis, Growth Mechanism, and Luminescence Properties

Abstract: LaCO(3)OH nano/microcrystals with a variety of morphologies/sizes including nanoflakes, microflowers, nano/microrhombuses, two-double microhexagrams sandwichlike microspindles, and peach-nucleus-shaped microcrystals have been synthesized via a facile homogeneous precipitation route under mild conditions. A series of controlled experiments indicate that the pH values in the initial reaction systems, carbon sources, and simple ions (NH(4)(+) and Na(+)) were responsible for the shape determination of the LaCO(3)O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 89 publications
4
106
0
Order By: Relevance
“…DTA curves showed that reactions (2) and (3) were endothermic. In addition, the endothermic peak for reaction (2) appeared at higher temperature for o-LaCO 3 OH than for h-LaCO 3 OH, whereas the opposite was observed for reaction (3). Figure 3 shows IR spectra of the h-and o-LaCO 3 OH powders.…”
Section: Ionsmentioning
confidence: 96%
See 4 more Smart Citations
“…DTA curves showed that reactions (2) and (3) were endothermic. In addition, the endothermic peak for reaction (2) appeared at higher temperature for o-LaCO 3 OH than for h-LaCO 3 OH, whereas the opposite was observed for reaction (3). Figure 3 shows IR spectra of the h-and o-LaCO 3 OH powders.…”
Section: Ionsmentioning
confidence: 96%
“…11 LaCO 3 OH powders have been also prepared by a hydrothermal reaction in an autoclave using the following reagents: LaCl 3 and thiourea, 12,13 La(NO 3 ) 3 and urea, 4,14 La(NO 3 ) 3 , glucose, and acrylamide, 15 La 2 O 3 and glycine, 16 LaCl 3 and gelatin, 17 La(oleate) 3 and aqueous tertbutylamine, 18 La…”
Section: -6mentioning
confidence: 99%
See 3 more Smart Citations